Potent and reversible open-channel blocker of NMDA receptor derived from dizocilpine with enhanced membrane-to-channel inhibition - Misiachna, Anna; Konecny, Jan; Kolcheva, Marharyta; Ladislav, Marek; Prchal, Lukas; Netolicky, Jakub; Kortus, Stepan; Zahumenska, Petra; Langore, Emily; Novak, Martin; Hemelikova, Katarina; Hermanova, Zuzana; et al. (Biomedicine & pharmacotherapy, 2024)
N-methyl-D-aspartate receptors (NMDARs) play a significant role in developing several central nervous system (CNS) disorders. Currently, memantine, used for treating Alzheimer's disease, and ketamine, known for its anesthetic and antidepressant properties, are two clinically used NMDAR open-channel blockers. However, despite extensive research into NMDAR modulators, many have shown either harmful side effects or inadequate effectiveness. For instance, dizocilpine (MK-801) is recognized for its powerful psychomimetic effects due to its high-affinity and nearly irreversible inhibition of the GluN1/GluN2 NMDAR subtypes. Unlike ketamine, memantine and MK-801 also act through a unique, low-affinity "membrane-to-channel inhibition" (MCI). We aimed to develop an open-channel blocker based on MK-801 with distinct inhibitory characteristics from memantine and MK-801. Our novel compound, K2060, demonstrated effective voltage-dependent inhibition in the micromolar range at key NMDAR subtypes, GluN1/GluN2A and GluN1/GluN2B, even in the presence of Mg2+. K2060 showed reversible inhibitory dynamics and a partially trapping open-channel blocking mechanism with a significantly stronger MCI than memantine. Using hippocampal slices, 30 µM K2060 inhibited excitatory postsynaptic currents in CA1 hippocampal neurons by ∼51 %, outperforming 30 µM memantine (∼21 % inhibition). K2060 exhibited No Observed Adverse Effect Level (NOAEL) of 15 mg/kg upon intraperitoneal administration in mice. Administering K2060 at a 10 mg/kg dosage resulted in brain concentrations of approximately 2 µM, with peak concentrations (Tmax) achieved within 15 minutes. Finally, applying K2060 with trimedoxime and atropine in mice exposed to tabun improved treatment outcomes. These results underscore K2060's potential as a therapeutic agent for CNS disorders linked to NMDAR dysfunction.
Keywords: Memantine; Humans; Electrophysiology; Receptors, N-Methyl-D-Aspartate; Hippocampus; lidé; zvířata; neurony; myši; Dizocilpine Maleate; hipokampus; Excitatory Amino Acid Antagonists; myši inbrední C57BL; Mice; receptory N-methyl-D-aspartátu; Male; Glutamate receptor; Antagonist; Mice, Inbred C57BL; Neurons; Excitatory Postsynaptic Potentials; antagonisté excitačních aminokyselin; dizocilpinmaleát; Animals; Pharmacokinetics; excitační postsynaptické potenciály; mužské pohlaví; Ion channel; memantin